Penerapan LKPD Mission Card Berbasis PBL: Upaya Peningkatan Sikap Kritis dan Kemampuan Menyimak Teks Aural - Umar, M. Jazuli; Purwati, Panca Dewi (YASIN, 2025)
Although listening skills and critical attitudes have received attention in several studies, research that specifically examines the integration of LKPD Mission Card, the Problem-Based Learning (PBL) model, and deep-learning-oriented listening activities in Bahasa Indonesia instruction at the elementary level remains limited. This study aims to describe the implementation of PBL-based LKPD Mission Card as an effort to improve fifth-grade students’ critical attitudes and aural text listening skills, as well as to evaluate its effectiveness in enhancing both aspects. A mixed-methods approach with an Explanatory Sequential design was employed, involving 14 fifth-grade students selected through total sampling. Data were collected using an Aural Comprehension Test (Tes Komprehensi Aural, TKA) in the form of multiple-choice and completion items, observation sheets of critical attitudes assessed by two observers, interviews, and documentation, and were analyzed using descriptive statistics and qualitative thematic analysis. The results show that the application of the PBL model supported by LKPD Mission Card is effective in improving listening skills, as indicated by an increase in classical mastery from 35.71% in the pretest to 92.86% in the posttest and a rise in the class mean score from 60.00 to 82.00. Students’ critical attitudes also developed positively, reflected in their ability to pose critical questions, express opinions logically, and relate the moral values of stories to everyday life, with the proportion of students in the high critical-attitude category increasing from 21.4% to 78.6%. The study concludes that PBL-based LKPD Mission Card plays an important role in strengthening critical attitudes and aural text listening skills, and implies that teachers and schools can adopt it as an alternative model and medium for Bahasa Indonesia instruction that supports deep learning in elementary schools.